PEMBARUAN HUKUM KELUARGA: WASIAT UNTUK AHLI WARIS (Studi Komparatif Tunisia, Syria, Mesir dan Indonesia) - Fatum Abubakar (State Institute of Islamic Studies (IAIN) Palu, 2011)
The Islamic law of inhreritance serves as one of the objects discussed in studies of Islamic law. However, the implementation of the Islamic law in the field of inheritance is not neccerally the same as that implemented in Muslim countires. The Muslim countries such as Tunis, Syria, Egypt and Indonesaia implement the Islamic law of inheritance but they do not possess the same understanding on the implementation of Islamic law of inheritance. The differencies lay on whoever elegible to receive the the property left by the dead persons and how many of the properties can be inherited; and whoever have the right to accept the inheritance from the dead person are among the questions discussed in this article in the respect of the implemenatiuon of Islamic law of inheritance in the four Muslim Countries.